Lessons learned from community-based resilience strategies applied to mitigate inconsistent potable water supplies in a selected village in Lepelle Nkumpi Local Municipality, Limpopo Province, South Africa - Muroa, Mmatseke Portia (My University, 2025)
The objective of the study was to investigate the mitigation strategies developed by residents of Mashite village in Limpopo Province to build resilience to the ongoing inconsistent potable water supply. The study involved an exploratory qualitative research approach collecting data from 15 participants using a semi-structured interview guide. The study employed an inductive thematic analysis based on face-to-face interviews. The findings of the research indicate that the participants have adopted several resilience strategies including household water storage facilities; sharing of water between households and purchasing water from local vendors. The participants also expressed their frustration with Lepelle-Nkumpi Local Municipality’s inability to deliver potable water especially that they are not informed when the potable water supply is on which means that they are unable to fill their water storage facilities. It is recommended that the Municipality communicates appropriately with residents to reduce this frustration.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2025
Keywords: Inconsistent potable water supplies; Resilience strategies; Community participation; Emergency water supply; Drinking water -- Water-supply; Drinking water -- Prices